Slow hydrodynamic regime to model B supergiant winds - Venero, Roberto Oscar José (2017)
Current hydrodynamic solutions for the winds of early-type stars are obtained from the theory of rotating stars with radiation-driven winds. These solutions are separated into two main branches: the fast solution and the slow solutions. The first set is the standard CAK solution, while the second set corresponds to a group of solutions with still poorly known properties. In this work we study the properties of the slow wind regime derived for different values of the line force parameters, and compute the resulting line profiles. Then we fit our synthetic line profiles with observed ones, in order to evaluate the ability of the slow solution to represent the variety of features observed in line profiles originated along the winds. We find that the winds of B supergiants can be well-represented by the slow regime, a result that could give new insights into the true nature of the outflows in early-type stars.